Solvent effect on the spectra of methylene green and methylene blue - Tchaikovskaya, Olga N.; Chaidonova, Vlada S.; Bocharnikova, Elena N.; Telminov, Evgenii N.; Dmitrieva, Natalia G; Ezhov, Dmitry M. (Journal of fluorescence)
This investigation focuses on dyes that differ only in the nitro substituent. The NO2 group leads to a strong hardening of the fluorescence at 298 K. In methylene green (MG) the excitation energy migrates to the system of triplet states. This nonradiative process causes the MG fuorescence absent or too low compared to methylene blue (MB). Moreover, laser-induced fluorescence is completely absent for MG in the investigated solvents. However, at liquid nitrogen temperature, we recorded fluorescence for MG in ethanol 250 times higher than at room temperature and phosphorescence too. The intensity of the MB fluorescence band in ethanol at 77 K is 6 times higher than at room temperature. According to the results of this study, the lifetime in the excited state decreases in the following order: isopropanol > acetonitrile≈ethanol≈dimethyl sulfoxide > > water for MG and chloroform > acetonitrile≈ethanol≈dimethyl sulfoxide > > water≈isopropanol for MB. In addition, MG has phosphorescence in ethanol at 780 nm and in chloroform at 810 nm.